The business of postcolonial immigration: marketing of immigration services in Punjab, India. Issue 4 (8th August 2022) - Mitra, Diditi
Abstract : In this paper, I show that immigration consulting agencies in the Doaba region of Punjab, India, mobilise the imaginary of the 'West' as a place to be successful and modern in order to sell their services. My focus is on the design of promotional materials created by the agencies that are well integrated into the visual landscape of this region. Thus I analyse this imaginary as presented in banners, posters, and signboards. The visual data is complemented with semi structured interviews conducted with staff and owners at the agencies, ethnographic observations as well as information gleaned from the agencies' websites. The study is novel in its exploration of the visual environment in pre-migration contexts where international migration is portrayed as a central path to prosperity. It is exploratory in nature and raises many questions for future researchers to pursue.